2008
DOI: 10.1585/pfr.3.s1031
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ion Confinement in Core Electron-Root Confinement (CERC) Plasmas in Large Helical Device

Abstract: An increase in ion temperature has been observed with superposition of centrally focused electron cyclotron resonance heating (ECRH) to plasmas heated by high-energy neutral beam injection (NBI) in Large Helical Device. The ion-temperature (T i ) rise is accompanied by the formation of electron internal transport barrier (ITB). A transport analysis shows that ion transport as well as electron transport is improved with the reduction of anomalous transport. A neoclassical ambipolar flux calculation shows a posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Transport analysis indicates that both electron and ion transport is improved in the core region with the reduction of anomalous transport. The toroidal rotation is driven in the co-direction by adding ECRH, and it is suggested that the spontaneous toroidal rotation is related to the transport improvement in the electron-root plasma [31]. Although the electron trans- port improvement is a common feature in the core electronroot confinement (CERC) plasmas [32], the ion transport improvement in CERC suggests a possible approach to achieve reactor-relevant high-temperature plasmas.…”
Section: Increase In Ion Temperature and The Related Ion Transportmentioning
confidence: 99%
“…Transport analysis indicates that both electron and ion transport is improved in the core region with the reduction of anomalous transport. The toroidal rotation is driven in the co-direction by adding ECRH, and it is suggested that the spontaneous toroidal rotation is related to the transport improvement in the electron-root plasma [31]. Although the electron trans- port improvement is a common feature in the core electronroot confinement (CERC) plasmas [32], the ion transport improvement in CERC suggests a possible approach to achieve reactor-relevant high-temperature plasmas.…”
Section: Increase In Ion Temperature and The Related Ion Transportmentioning
confidence: 99%